The Impact of Government Measures on Business Development in the ICT Sector - Bestvina Bukvić, Ivana; Đurđević Babić, Ivana (International Journal of Industrial Engineering and Management, 2021)
The purpose of this paper is to identify which economic measures do ICT experts perceive as important for the development of the ICT sector and to explore whether there is a need to introduce special developmental measures depending on the international or domestic market orientation. To gain valuable results, a survey on 112 ICT experts was conducted and, along with descriptive statistics measures, a chi square test and association rules were used in the analysis. The results of the primary research indicate variables that need to be addressed in the development of new policies (primary reduction of bureaucratization, taxation and frequency of legal changes) and obviates the need for introducing separate policies for internationally oriented companies. Article history: Received (November 12, 2020); Revised (February 23, 2021); Accepted (February 24, 2021); Published online (March 04, 2021)